Quantitative Investigation on the Contributing Factors to the Contact Angle of the CO2/H2O/Muscovite Systems Using the Frumkin-Derjaguin Equation - Masashige Shiga; Masaatsu Aichi; Masao Sorai (Geofluids)
It is significant to understand the values and trends of the contact angle of CO2/brine/mineral systems to evaluate and model the sealing performance of CO2 Geo-Sequestration (CGS). It has been reported that the contact angles of the CO2/brine/muscovite systems increase as pressure increases from ambient conditions to reservoir conditions. This trend suggests a decrease in seal integrity. In this paper, we studied its mechanisms and the contributing factors by calculating the Frumkin-Derjaguin equation, which is based on the thermodynamics of the interfacial system. Results show that a decrease of pH is a critical factor for the wettability alteration at a lower pressure range (0.1 MPa to 3.0 MPa). In contrast, the increase of CO2 density and the decrease in the interfacial tension of CO2/brine are significant for the wettability change at a higher pressure range (3.0 MPa to 10.0 MPa). Also, sensitivity analysis shows that the contact angle is sensitive to the interfacial tension of CO2/brine and the coefficients of hydration forces.